A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Sierra Nevada de Santa Marta, Colombia - Provenzano R., Francisco; Milani, Nadia; Ardila R., Carlos (Zootaxa, 2017)
As a part of an assessment of loricariid catfishes inhabiting the Andes of Colombia, specimens belonging to an interesting new species were identified. The new species is described herein, and it is tentatively included in the genus Cordylancistrus. The new species can be easily distinguished among its congeners by the presence of a unique diagnostic character: a fleshy keel or excrescence, black or dark brown, over the posterior tip of supraoccipital. Specimens of the new species were captured in rivers of the Sierra Nevada de Santa Marta and the Sierra de Perijá that drain to the Magdalena River Basin and Caribbean Sea. The occurrence of one species of Cordylancistrus in the Sierra Nevada de Santa Marta could have interesting biogeographic implications for hypotheses related to the geological history of northwestern corner of South America or to the dispersal or vicariance models used to explain biogeographical patterns of related species in Colombia.